ABORSI DALAM PERSPEKTIF HUKUM ISLAM (Meluruskan Problema Perempuan di Mata Publik) - Fatmawati, Fatmawati (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2016)
Abortion is not just a medical problem or public health, but also the social problems that arise because people follow the Western civilization. But the solution must be comprehensive, fundamental, radical, which is essentially the attitude? taqlid? to revoke the West with all the values and institutions of the West in conflict with Islam, and then replaced with the Islamic civilization is humane and fair. For women, abortion is a very frightening because it related to someone living dead. However, under certain conditions, women in a dilemma, love or grief? Continue to maintain trust God, or must be prepared to suffer? Islam is a religion of peace. He attended a reference to human safety. For that reason, Islam Syariat also very flexible and supple. Syariat Islam does not necessarily proscribe something that God has forbidden on certain conditions, but will still refer to the social conditions that encompass these problems.